Tradisi Fida’an dan Akulturasinya pada Masyarakat Desa: Kajian Living Hadis di Plosojenar Ponorogo - Ali Mahfuz Munawar; A Fadly Rahman Akbar (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2023)
Fida’an is an activity carried out by Javanese Muslims after the death of one of their community member. The activity consists of reciting the Quranic verses of al-Ikhlas a thousand times or the tahlil up to 71.000 times which is addressed to the deceased to avoid the torment of the fires of hell and get holy rewards. This study seeks to find out the views of the people of Plosojenar Village, Kauman District, Ponorogo Regency regarding fida’an by inquiring (1) What and how is the practice of fida’an among people of Plosojenar? and (2) How do the people of Plosojenar associate fida’an practices with hadith texts? In this study, the authors used the method of observation, interviews, and documentation to obtain supporting data. The data analysis used was descriptive qualitative with a phenomenological approach to religion and anthropology of religious symbols by examining the concept of diversity in the symbols present in the ritual. The results of the study concluded that (1) the meaning of fida’an for the Plosojenar people is divided into two parts, namely burdening good deeds and freeing from the torment of hellfire; and (2) the community's view of fida’an is diverse such as getting rewards and guaranteed by Allah Swt to avoid hell, as well as the growth of togetherness, help, friendship and charity within the community.